2015
DOI: 10.1681/asn.2014060535
|View full text |Cite
|
Sign up to set email alerts
|

Furosemide Stress Test and Biomarkers for the Prediction of AKI Severity

Abstract: Clinicians have access to limited tools that predict which patients with early AKI will progress to more severe stages. In early AKI, urine output after a furosemide stress test (FST), which involves intravenous administration of furosemide (1.0 or 1.5 mg/kg), can predict the development of stage 3 AKI. We measured several AKI biomarkers in our previously published cohort of 77 patients with early AKI who received an FST and evaluated the ability of FST urine output and biomarkers to predict the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
157
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 229 publications
(171 citation statements)
references
References 32 publications
8
157
0
6
Order By: Relevance
“…Neben der mittels Kreatinin ("Nierenfunktionsmarker") diagnostizierten AKI erscheint auch das Konzept der "subklinischen AKI" relevant, das über renale Biomarker ("Nierenschä-digungsmarker") diagnostiziert werden kann, bevor es sich klinisch über einen Kreatininanstieg äußert [27]. Auch ohne diagnostischen Anstieg des Kreatinins konnte mittels Biomarker, die einen Zellschaden oder -stress anzeigen, ein [26,40].…”
Section: Hintergrundunclassified
“…Neben der mittels Kreatinin ("Nierenfunktionsmarker") diagnostizierten AKI erscheint auch das Konzept der "subklinischen AKI" relevant, das über renale Biomarker ("Nierenschä-digungsmarker") diagnostiziert werden kann, bevor es sich klinisch über einen Kreatininanstieg äußert [27]. Auch ohne diagnostischen Anstieg des Kreatinins konnte mittels Biomarker, die einen Zellschaden oder -stress anzeigen, ein [26,40].…”
Section: Hintergrundunclassified
“…Interestingly, although plasma neutrophil gelatinase-associated lipocalin (NGAL) might improve the prediction of WKF, the biomarker had a similar performance to serum creatinine [5]. Furthermore, the follow-up of the furosemide stress test study found limited performance of biomarkers to predict WKF, which were largely outperformed by the furosemide stress test [6].…”
Section: Assessment Of Renal Prognosis and Of Renal Functionmentioning
confidence: 99%
“…Interestingly, although plasma neutrophil gelatinase-associated lipocalin (NGAL) might improve the prediction of WKF, the biomarker had a similar performance to serum creatinine [5]. Furthermore, the follow-up of the furosemide stress test study found limited performance of biomarkers to predict WKF, which were largely outperformed by the furosemide stress test [6].The gold standard for glomerular filtration rate (GFR) determination is inulin clearance, but this cannot be measured easily. Carlier and co-workers compared inulin clearance with creatinine clearance and several creatinine and/or cystatin C-based GFR equations in 68 critically ill patients with stable kidney function.…”
mentioning
confidence: 99%
“…Assessment of urine output following an FST challenge (protocoled dose of a diuretic in the setting of early AKI) has demonstrated the ability to improve patient risk stratification for adverse outcomes (AKI progression, need for RRT, and inpatient mortality) [12]. In fact pairing functional and structural injury markers (as suggested by a recent Acute Dialysis Quality Initiative consensus paper) such as NGAL and TIMP2*IGFBP7 with the FST improves their accuracy in detecting these impending adverse events [13]. Others have shown that combining the risk stratification of the renal angina index with biomarkers enhances the detection of those at highest risk for morbidity and mortality [11].…”
mentioning
confidence: 99%